GAMBARAN KADAR GULA DARAH SEWAKTU DAN TINGKAT PENGETAHUAN MASYARAKAT DUSUN PIMPINGA DESA BATURAPPE KECAMATAN BIRINGBULU KABUPATEN GOWA - Rahmawati Rahmawati; Andi Fatmawati; Nurhidayat Nurhidayat; Atri Rahmi (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2023)
Blood sugar is a medical term that can determine the level of glucose in the blood. Health tests such as blood sugar checks are markers or tools to identify metabolism in the body. Glucose levels usually rise after eating and usually fall before eating. This service activity aims to find out the description of current blood sugar levels (GDS) and the level of knowledge of the people of Pimpinga Hamlet, Baturappe Village, Biringbulu District, Gowa Regency. Examination of GDS with the POCT method using a kit (Gluco-test) or glucometer. The number of participants was around 56 people and there were more women than men. Before carrying out the GDS examination, interviews were conducted with participants to explore medical history or hereditary diseases. The examination results showed that there were 42 participants (75%) who had normal blood sugar levels, and 14 participants (25%) who had blood sugar levels above normal values (> 200 mg/dl). Thus it can be concluded that the normal blood sugar levels (GDS) of the community members are generally normal because they have paid attention to the pattern of healthy food intake by consuming vegetables.